Phyllochron, and root system development of six strawberry cultivars with different photoperiodic flowering responses - Chiomento, José Luís Trevizan; Ferreira, Ana Flávia Baccarin; Costa, Rosiani Castoldi; dos Santos Trentin, Nicolas; dos Santos Trentin, Thomas; Calvete, Eunice Oliveira (Scientia Agraria Paranaensis, 2021)
Bare-root strawberry plants produced in Patagonia accumulate more reserves in the main crown, which allows their immediate development after transplantation. Due to the dependence on these bare-root plants, Brazilian producers use early cultivars, which start the leaves emission and the flower buds differentiation in advance, since these bare-root plants do not always arrive within the estimated time for planting in southern Brazil. The objective of the work was to investigate whether six strawberry cultivars, produced in a greenhouse, differ in their phyllochron, and root system development. Six cultivars were tested, arranged in a randomized block design, with four replications. Bare-root plants were cultivated in soil in a greenhouse. The phyllochron was evaluated by counting the number of leaves, weekly, from the beginning of leaf emission (from the main crown) until the appearance of the first fruit. The roots were digitized by a scanner and the images analyzed by the WinRHIZO® software. ‘Camarosa’ cultivar was considered the earliest to start fruiting, as it had the lowest phyllochron value (69.93ºC day-1 leaf-1), while the cultivar ‘San Andreas’ was the latest (166.67ºC day-1 leaf-1). ‘Albion’ and ‘Aromas’ presented the highest total root length in relation to the other cultivars. In conclusion, the six strawberry cultivars analyzed in this study, with different photoperiodic classifications regarding flowering, differ in relation to their morphophenological performance. In the growing conditions of southern Brazil, phyllochron study indicates that ‘Camarosa’ cultivar is the earliest and ‘San Andreas’ cultivar is the latest. ‘Albion’ and ‘Aromas’ cultivars are more compact plants, with greater potential for the development of the root system.